Cysteine proteases secreted by the pinewood nematode, Bursaphelenchus xylophilus: In silico analysis. (December 2018) - Cardoso, Joana M.S.; Fonseca, Luís; Egas, Conceição; Abrantes, Isabel
Graphical abstract: Highlights: BxCP3 and BxCP11 are cathepsin L-like proteins. BxCP7 and BxCP8 are cathepsins B proteins. These four BxCP are pro-enzymes that become active after N-terminal removal. BxCP7 and BxCP8 have an occluding loop unique of cathepsin B proteases. Abstract: The pinewood nematode, Bursaphelenchus xylophilus, is an important plant-parasitic nematode responsible for the development of the pine wilt disease and recognised as a major forest pest. Previous studies on the comparison of B. xylophilus and B. mucronatus secretomes obtained under maritime pine, Pinus pinaster, wood extract stimulus revealed that several cysteine proteases were increased in B. xylophilus secretome. In nematodes, proteases are known to play critical roles in parasitic processes like tissue penetration, digestion of host tissues for nutrition and evasion of host immune response. To gain further insight into the possible role of cysteine proteases on B. xylophilus pathogenicity, the molecular characterisation of four secreted cysteine peptidases was performed. BxCP3 and BxCP11 were identified as cathepsin L-like proteins and BxCP7 and BxCP8 as cathepsin B proteins. Only BxCP8 revealed high homology with another B. xylophilus cathepsin B referred on GenBank, all the others differ from the closer proteins deposited in this database. In silico three-dimensional structures of the four BxCP suggest that these proteins are pro-enzymes that become active when the pro-peptide is cleaved. BxCP7 and BxCP8 predicted structures revealed the presence of an occluding loop that occludes the active site cleft, typical of cathepsin B proteases.